Audit Quality of Pandemic Era Public Accounting Firms - Budiandru, Budiandru (Universitas Negeri Semarang, 2021)
The purpose of this study is to analyze the effect of due professional care, accountability, and reputation of public accounting firms on audit quality during a pandemic. Data were collected using a questionnaire and processed using multiple linear regression with a sample of auditors and students who have worked in public accounting firms in Jakarta. The processing results show that due professional care, accountability, and office reputation significantly affect audit quality during a pandemic. The accounting firm can maintain and improve audit quality by providing education and training to auditors and providing incentives according to performance achievements. Keywords: Due Professional Care; Accountability; Reputation; Audit Quality